Radiological patterns and pulmonary function values of lung involvement in primary Sjögren’s syndrome: A pilot analysis - Mormile, Ilaria; Mormile, Mauro; Rossi, Francesca Wanda; Williams, Michela; Valente, Tullio; Candia, Claudio; Granata, Francescopaolo; Rega, Roberto; Orlandi, Martina; Matucci-Cerinic, Marco; Molino, Antonio; de Paulis, Amato (Frontiers in Medicine, 2022)
Background: Lung involvement in primary Sjögren’s syndrome (pSS) may vary from 9 to 90%. Interstitial lung disease and tracheobronchial alterations are the most typical findings. The evidence of primarily emphysematous changes at computed tomography of the chest of pSS patients has occasionally been described but poorly characterized. This study aims to assess pulmonary involvement and the impact on respiratory function in a cohort of pSS patients. Methods: 22 consecutive patients diagnosed with pSS underwent pulmonary function tests to investigate the presence of ventilatory impairment and evaluate the exchanges of alveolar gases. All patients underwent a chest High-Resolution Computed Tomography (HRTC). Results: Dynamic volumes were within the normal range in 21 patients (95.4%). A reduction in the diffusing capacity of the lung for carbon monoxide (DLCO) was observed in 18 patients (81.8%). Ten (45.5%) patients showed a mild degree deficit, while 8 patients (36%) showed a moderate degree deficit. Analysis of DLCO revealed a significant difference between pSS patients and controls [t(30.98)=-10.77; p<0.001], showing a higher DLCO value for the healthy controls (mean ± SE; 101.27 ± 6.08) compared to pSS patients (mean ± SE; 65.95 ±12.78). Emphysema was found in 21 (94.5%) patients and was the most widespread pulmonary injury. Tracheal thickness was reduced in 15 (67%) patients. Micronodules were observed in 10 (45%) patients in all the pulmonary fields. Bronchial wall thickening and bronchiectasis were observed in 8 (36%) patients, mainly in the lower lobes. Ground glass was found in 5 (22.5%) patients in lower and higher lobes. Cysts were observed in 2 patients (9%). Conclusion: The reduction of the DLCO could be related to early emphysematous alterations in the absence of spirometric alterations and relevant respiratory symptoms. In conclusion, emphysema might be seen as an early pulmonary involvement mark in patients suffering from pSS.